IMPLEMENTATION OF URBAN TRANSPORTATION POLICY BASED ON LAW NO. 22 YEAR 2009 ON ROAD TRAFFIC AND TRANSPORTATION - Alwi Alwi (Masalah-Masalah Hukum, 2012)
Abstract Problem of urban transportation is acrucial issue in thesocio-economicof urban society in Indonesia. These problems such as congestionan dtrafficclutter of urban transportation which raises economic lossesusers’ society are not few in number. This problem still appears, but government policies and derivatives regulations which followed been implemented. In addition, the delegation of authority on urban transportation to Local Government has been done, as regulated in Law 22 of 2009, which is aconcrete manifestation of the policy of regional autonomy but this issue not yetresolved with effectively.Therefore, the required development and law enforcement in the implementation of urban transport policy in Indonesia.   Key word:  public transportation, urban transportation, public service   Abstrak Masalah angkutan kota merupakan masalah krusial dalam kehidupan social ekonomi masyarakat kota di Indonesia. Masalah ini seperti kemacetan dan kesemrawutan lalu lintas angkutan kota yang menimbulkan kerugian ekonomi masyarakat pengguna yang tidak sedikit jumlahnya.  Masalah ini tetap saja muncul namun kebijakan pemerintah dan berbagai peraturan deripatif yang mengikutinya telah diimplementasikan. Di samping itu, pendelegasian kewenangan angkutan kota ke Pemerintah Daerah telah dilakukan,  sebagaimana diatur dalam UU No. 22 Tahun 2009, yang merupakan wujud nyata dari kebijakan otonomi daerah, tetapi masalah ini belum terselesaikan dengan efektif. Oleh karena itu, diperlukan pembinaan danpenegakan hokum dalam implementasi kebijakan angkutan kota di Indonesia.   Kata Kunci: angkutan publik. Angkutan kota, pelayanan publik